Clean energy microgrids - Obara, Shin'ya; Morel, Jorge, 1974- (IET energy engineering series ;, 2017)
This book describes the latest technology in microgrids and economic, environmental and policy aspects of their implementation, including microgrids for cold regions, and future trends. The aim of this work is to give this complete overview of the latest technology around the world, and the interrelation with clean energy systems.